DELAY IN DIAGNOSIS AND TREATMENT OF BENIGN PAROXYSMAL POSITIONAL VERTIGO IN CURRENT PRACTICE - Arshad, Muhammad; Abbas, Shujaat; Qureshi, Ishaq Ahmad (Journal of Ayub Medical College Abbottabad, 2013)
Background: More than 50% of the patients with peripheral vestibular disorders are suffering from Benign Paroxysmal Positional Vertigo (BPPV). Diagnosis is established by positive Dix-Halpike test and/or roll test. Objective of this study was to analyse the delay in diagnosis and treatment of BPPV in current practice and to suggest measures to avoid this delay. Methods: One hundred and fifty two consecutive patients who were diagnosed and treated for BPPV in ENT department CMH Rawalpindi from Jan 2009 to Sep 2011 were selected for this study. All these patients were interviewed in detail regarding duration of vertigo, associated symptoms, visits to hospitals, investigations, treatment taken, cost of treatment and last or referral diagnosis before coming to our department. Results: Out of 458 patients who presented with vertigo, 152 (33.2%) fulfilled the diagnostic criteria of BPPV. Male to female ratio was 1:1.17. Age range was 13-80 years and mean age 58.2±12.6. Posterior canal was affected in 96.7% and lateral canal in only 3.3%. Average duration between onset of first symptoms and diagnostic positional test was 19 months. One hundred and thirty eight patients have been visiting to general practitioners, various specialists, Homeopaths and Hakeems. Only 21% patients had visited to ENT specialists. 15.2% patients were already labelled correct diagnosis mostly by ENT specialists but Halpike test was done only in 8 patients and Epley's manoeuvre was tried in only four patients. 16.4% patients had undergone costly investigations like CT scan and MRI. Average cost on treatment before final diagnosis was Rs. 13,500 per patient. Particle repositioning procedure was successful in 84% patients in first attempt and 96% in two attempts. Conclusion: Though BPPV is a common and easily treatable condition, its diagnosis and treatment is delayed because of lack of awareness of this condition among doctors and patients. Clear understanding of the patho-physiology, diagnostic positional tests and canalith repositioning manoeuvre should be achieved through lectures and demonstrations. Keywords: Positional vertigo, Benign paroxysmal positional vertigo, Positional test, Repositioning manoeuvre, Semicircular canal